Serum leptin levels are higher but are not independentlyassociated with severity or mortality in the multipleorgan dysfunction/systemic inflammatory responsesyndrome: a matched case control and a longitudinalstudy - Papathanassoglou, Elizabeth; Moynihan, Jan; Ackerman, Michael John; Mantzoros, Christos S. (My University, 2001)
OBJECTIVE Hypercatabolism and immune dysfunc-tion are closely associated with the development ofsystemic inflammatory response±multiple organdysfunction (SIRS/MODS) in critical illness. It remainsunclear however, whether leptin, an adipocyte-derived hormone whose levels are influenced byseveral cytokines and which regulates immune func-tion, food-intake and energy expenditure is indepen-dently related to the development of and/or severityand mortality from SIRS/MODS.DESIGN and PATIENTS To assess the role of leptin inSIRS/MODS we performed a matched case controland a longitudinal study (14 days) in 35 critically illpatients with SIRS/MODS and 35 matched controls.RESULTS Baseline leptin levels were positivelyassociated with body mass index (BMI) and TNF-a(P , 0´01) in patients and with IGF-1 and IL-6 levels(P , 0´05) in controls. Furthermore, leptin levelsexhibited a progressive increase from the first tothe last day of the study and although baseline levels were not different, peak leptin levels as well as leptinlevels on the last day of the study were significantlyhigher in cases than in controls (P , 0´05). TNF-alevels, IL-6 and cortisol levels were also higher,whereas IGF-1 levels were lower in cases (P , 0´05).To assess whether leptin levels are independentlyassociated with SIRS/MODS we performed multi-variate logistic regression analysis which revealedthat leptin up-regulation in cases is mediated byelevated TNF-a and cortisol levels. Finally, there wasno independent association between leptin andsurvival in this group of critically ill patients.CONCLUSION We conclude that cytokines and corti-sol upregulate leptin levels, which may contributeto the development of the hypercatabolism, wastingand immune dysfunction but leptin levels are notindependently associated with severity or mortalityof patients with systemic inflammatory response±multiple organ dysfunction.
Keywords: Hypercatabolism; Immune dysfunction; Leptin; Tumor necrosis factor alpha